Controlled synthesis of nickel sulfide polymorphs: studies on the effect of morphology and crystal structure on OER performance. (June 2020) - Manjunatha, C.; Srinivasa, N.; Chaitra, S.K.; Sudeep, M.; Chandra Kumar, R.; Ashoka, S.
Abstract: Herein, the Taguchi L-9 orthogonal technique has been employed to design the optimised conditions (sulfur source, temperature, reaction time and surfactant) for the preparation of nickel sulfide polymorphs using hydrothermal method. The experimental results demonstrate the temperature dependant phase transition of NiS → Ni3 S4 → NiS2 and the prepared nickel sulfide polymorphs exhibit distinctive morphologies of sugar cubes, spherical apple, rose type, aggregated stones, and tubular bacteria type structures. The effect of morphology and crystalline structure on oxygen evolution reaction (OER) has been investigated for the first time where the OER performance follows the order: NiS > NiS2  > Ni3 S4 . Among the various morphologies of NiS, and NiS2, the order of OER performance is as follows: NiS(sugar-cubes)  > NiS(agglomerated stone particles)  > NiS(apple shaped) and NiS2(aggregated stoneparticles)  > NiS2(rose type)  > NiS2(tubular bacteria) shaped nanostructure. Graphical abstract: Image 1 Highlights: Temperature dependant phase transition of NiS.→ Ni3 S4 → NiS2 Nickel sulphide polymorphs exhibit distinctive morphologies. OER performance: NiS(sugar-cubes) >NiS(agglomerated stone particles) >NiS(apple shaped) . OER performance: NiS2(aggregated stone particles) >NiS2(rose type) >NiS2(tubular bacteria) . The NiS/SPE displayed an OER overpotential of 362 mV at 20 mA cm −2 .